Naši podestaji - Mlakar, Boris (Studia Historica Slovenica, 2017)
In this piece, based on original archive material, the author presents an overview of the leadership of municipal administration in the territory of the Julian province in the period after 1926 when municipal self-governance was abolished, and the election of mayors and municipal councils was replaced by centralist appointments of so called podesta and their advisory committees. Because the period coincided with the process of intense Italianisation of the Slovenian population and the simultaneous permeation of society by fascism, the author tries to establish, if any of the podesta were after all persons of Slovenian origin, how many there were, in which municipalities and of course what condition they had to fulfil besides the unavoidable membership in the fascist party. The overview lists each region in Slovenian Littoral separately, and uses as a criterium for establishing the national origin of the podesta their surnames since despite the Italianisation they are still quite recognisable.
Keywords: centralizem; fašizem; Julijska krajina; Primorska; Slovenci; župani